Silk route now through Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The wild silkworm in Africa could soon be a serious competitor to Chinese and domestic silkworms (Bombyx mori). Wild silk demands high prices, but in many African communities the worms are consumed without knowing their worth as the source of...